The Sustainable Consumption Beheviors of Generation X and Generation Y Groups in Nonthaburi Province - Imprasert, Karanpat (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this study were to 1) study the level of sustainable consumption behavior of generation X and generation Y in Nonthaburi province, and 2) to compare the sustainable consumption behavior of generation X and generation Y in Nonthaburi province. A questionnaire was used as a tool for collecting data from 400 samples. Statistics used in data analysis were frequency, percentage, mean, standard deviation, and t-test. The research results found that: 1) the level of sustainable consumption behavior; the economic dimension, in general, was at the level of accomplishment every time. Social dimension, in general, was at the level of accomplishment often. The environmental dimension, in general, was at the level of frequent use. 2) Generation X and generation Y had different sustainable consumption behavior in the economic dimension, social dimension, and environmental dimensions statistically significant at the .05 level.